HAK-HAK PEREMPUAN DALAM AL-QUR'AN: LARANGAN KDRT DAN PERLINDUNGAN KELUARGA - Dohe, Muh. Ilham Majid; Abubakar, Achmad; Mahfuz, Muhsin (Jawa Timur: Prodi. Ilmu Al Quran dan Tafsir Fakultas Ushuluddin IAI Tarbiyatut Tholabah, 2025)
Domestic violence within Muslim societies continues to persist not only as a social and legal problem but also as a consequence of entrenched interpretive practices that normalize patriarchal authority in family relations. This study critically examines women’s rights and the Qur’anic prohibition of domestic violence through a maqāṣid al-sharīʿah–based hermeneutical framework. The primary objective is to elucidate the ethical architecture of the Qur’an in regulating family relations and to develop an interpretive model that situates domestic violence as fundamentally incompatible with the higher objectives of Islamic law. Employing a qualitative normative approach, this study conducts a thematic analysis of Qur’anic verses on family relations, supported by classical and contemporary Qur’anic exegesis and strengthened through a comparative analysis of legal instruments and family protection policies. The data are integratively constructed from the Qur’anic text, representative exegetical literature, and legal documents addressing domestic violence. The findings demonstrate that the Qur’an consistently frames the family as an ethical space grounded in justice (ʿadl), compassion (raḥmah), and human dignity (karāmah), thereby rendering all forms of domestic violence contradictory to the protection of life, honor, and family integrity as core objectives of the Sharīʿah. This study contributes by proposing an integrative maqāṣidī hermeneutical framework that bridges Qur’anic ethics, gender-sensitive interpretation, and contemporary legal discourse, offering a normative foundation for advancing family justice and protection in Muslim societies.